ANALISIS PENGARUH BAURAN PROMOSI TERHADAP PENJUALAN ROKOK DI CV. AYUNDA PERMATA SEJAHTERA DESA LAWANGAN DAYA KECAMATAN PADEMAWU KABUPATEN PAMEKASAN - Agustina, Puput; Sustiyana, Sustiyana; Ningsih, Kustiawati; Nazizah, Fitrotin (Universitas Islam Madura, 2024)
The tighter and sharper competition in the cigarette industry, causing companies to strive so that the products produced can be sold and can dominate the market and get optimal profits. The purpose to be achieved in this study is to find out the picture of promotion implementation and to determine the effect of promotion with sales volume through a promotion mix, namely, public relations, advertising, sales promotion, individual sales, direct sales. In this study, a quantitative descriptive research method was used that used a survey method. The location of the research was carried out deliberately based on the consideration that in Lawangan Daya Village this is the place of the CV Cigarette Marketing Office. Ayunda Permata Sejahtera. The instruments in this study were questionnaires and Likert scales. The respondents in this study numbered 30. The data analysis used was multiple linear regression. The results showed that public relations had a calculated t value< t table (0.206<1.69), advertising had a calculated t value< t table (2.495>1.69), individual sales had a calculated t value< t table (0.963<1.69), sales promotion had a calculated t value< t table(1.714>1.69), direct sales had a calculated t value< t table (3.598>1.69). Of the five variables used, there are two influential variables that have a real influence on increasing sales, namely public relations, individual sales.